Republic of Korea : 2021 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for the Republic of Korea. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2021)
Korea entered the COVID-19 pandemic with sound macroeconomic fundamentals and a resilient financial system. The initial outbreak led to a sharp decline in economic activity and employment and generated substantial economic slack. With the help of an effective COVID-19 containment strategy and comprehensive economic policy response, the overall impact was smaller than in peers, with real GDP growth in 2020 of -1.0 percent. The economy is projected to grow 3.4 percent in 2021, albeit at varying speeds across sectors, and with a high degree of uncertainty centered on the speed of normalization in the COVID situation. Public debt has risen and deficits have widened but remain at manageable levels. Credit continues to grow rapidly, financial markets have normalized quickly, and the financial sector has remained relatively sound to date despite the pandemic. The authorities are pursuing greener and more digital growth, along with a stronger social safety net, through the Korean New Deal.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet